The Resilience Of E-Learning Based Merdeka Curriculum Training Effectiveness For Islamic Religious Education Teachers In Improving Learning Quality At Man Landak - Sulistyowati, Dewi; Wahab, Wahab; Prabowo, Sugeng Sulistyo (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Although existing literature on e-learning in PAI (Islamic Religious Education) often highlights its effectiveness, available insights remain limited regarding the resilience aspect of training programs, especially for teachers implementing the Merdeka Curriculum in resource-constrained 3T (frontier, outermost, and underdeveloped) regions. Thus, the purpose of this research is to analyze the resilience and effectiveness of e-learning-based training for the implementation of the Kurikulum Merdeka in improving the quality of learning by Islamic Religious Education teachers at MAN Landak. This research employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The findings reveal that e-learning training significantly improves the pedagogical and professional competencies of PAI teachers. The training has proven resilient to changes in educational contexts and contributes positively to learning quality, as evidenced by increased student engagement, diverse teaching methods, and improved learning outcomes. The study highlights that such training demonstrates significant resilience to change, leading to improved PAI learning quality. Specifically, the e-learning program not only enhanced teachers' technical skills but also cultivated a new learning culture, fostering reflective, innovative, and continuously self-developing teachers prepared for 21st-century educational challenges. Furthermore, the e-learning method was found to be highly effective, especially within the Merdeka Belajar framework where practice is integral. This was evidenced by high student learning interest and increased engagement through practical application, which provided meaningful and in-depth learning experiences. The implementation of e-learning is deemed highly effective in delivering learning within the framework of the Kurikulum Merdeka.